SMART SYSTEM FARMING MANAGEMENT : FINTECH ASPECTS IN PRODUCTION AND MARKETING AT EDRIAN BULE FARM LAMPUNG - Rachman, Muhamad Emil; Anggraini, Sari; Maksum, Asep; Mega, Selfia Alke (AGROTEKSOS; Vol 35 No 3 (2025): Jurnal Agroteksos Desember 2025DO - 10.29303/agroteksos.v35i3.1511, 2025)
The development of technology-based livestock farming is increasingly being driven by government programs that focus on digitization, productivity improvement, and the integration of modern technology in livestock management. These initiatives include training, the provision of digital platforms, and infrastructure support to strengthen the livestock supply chain. However, their implementation in the field still faces various obstacles, such as limited internet access and the high cost of technological devices. In addition, low digital literacy and readiness to adopt technology among farmers are also challenges that need to be overcome. Translated with DeepL.com (free version)This study aims to develop an integrated livestock management model using Smart System Farming Management and FinTech technologies to improve production and marketing efficiency at Edrian Bule Farm in Lampung. Using a grounded theory approach, this study explores the challenges faced by farmers in managing production and finances and how technology can be used to overcome these problems. Through inductive qualitative data analysis, this study successfully identified the main needs of farmers in terms of production and financial management, as well as the factors that influence technology adoption. The results of this study are expected to provide an overview of the influence of financial knowledge and technology or FinTech on livestock businesses, particularly in Lampung Province, and to understand the role of integration between smart agricultural technology and digital-based financial solutions that can improve operational efficiency, expand market access, and facilitate access to financing for small to medium-scale farmers.